DIGITAL AGE LITERACY FOR INDONESIAN ELEMENTARY SCHOOL STUDENT - Soufi Dianimdri Dianimdri; Wahyu Dwi Yuliani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Education in the digital age demands students to have adequate literacy skills. NCREL & Metiri Group (2003), in EnGauge 21st Century Skills, states that literacy in the digital age includes several components, ranging from the basic scientific literacy, economic literacy, technological literacy, visual literacy, information literacy, multicultural literacy, to the global-awareness. Literacy in Indonesia is low compared to other countries. Therefore, digital literacy as part of 21st century education is important since elementary school. The review of this article will further discuss the application of aspects of the digital literacy domain in primary school learning. In the end, the implementation of digital literacy requires the synergy of various parties, they are: government, schools, parents, and society.